Serum untargeted metabolomics alterations in systemic lupus erythematosus patients with elevated serum ferritin - Na Li; Rui Chai; Xue Xu; Qian Xu; Jun Liang; Dandan Wang; Huayong Zhang; Xuebing Feng; Linyu Geng; Lingyun Sun (Scientific Reports)
Abstract This study investigated the alterations in serum metabolic profile in systemic lupus erythematosus (SLE) patients with increased levels of serum ferritin. 52 SLE patients were divided into two groups based on their ferritin levels. The metabolomic profile was identified using non-targeted metabolomics technology (UHPLC-MS/MS), and analyzed by Principal Component Analysis (PCA), Orthogonal Partial Least Squares Discrimination Analysis (OPLS-DA), ROC analysis, and pathway analysis. Results showed that SLE patients with high ferritin levels had increased hematologic involvement and elevated levels of inflammatory markers, including procalcitonin (PCT), alanine transaminase (ALT), and aspartate transaminase (AST). Additionally, there was decreased levels of albumin and CD4+ T cell counts. A distinct metabolic profile was found in the high-ferritin SLE group, with significant changes in metabolites and metabolic pathways. Potential correlations between differential metabolites and clinical features were identified, including associations with PCT, interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), albumin, ALT, AST, immunoglobulin G (IgG), and CD3+CD4+ T cell. The findings confirm elevated serum ferritin is associated with hematology involvement and offer insights into the pathology and targeted therapeutic strategies of SLE.